Physiological Parameters and Development of Passion Fruit Subjected to Water Stress and Propagation Methods - Cavichioli, José Carlos; Lisboa, Lucas Aparecido Manzani [UNESP]; Vitorino, Rodrigo Aparecido; Contiero, Leandro Aparecido Fogagnoli [UNESP]; de Figueiredo, Paulo Alexandre Monteiro [UNESP]; Rocha, Edison Alves [UNESP] (FapUNIFESP (SciELO), 2022)
The aim of this work was to evaluate the physiological parameters and development of passion fruit submitted to water stress and propagation methods. The experiment was conducted in a completely randomized design (DIC), in a 3x3 factorial arrangement, using methods of propagation (PM) of passion fruit, which are: the species Passiflora edulis propagated with seeds (PS); Passiflora edulis grafted on the Passiflora gibertii species propagated by seed (E x PS) and Passiflora edulis grafted on the Passiflora gibertii species propagated by cuttings (E x PE) and interacting with three irrigation intervals (I), which are irrigated with intervals of 4, 8 and 12 days, with four repetitions. The suspension of irrigations for eight days reduces the rate of CO2 assimilation, transpiration and stomatal conductance in passion fruit seedlings propagated by seeds and grafting. Passion fruit plants propagated by seeds show greater efficiency in the use of water than those grafted on P. gibertii. Passion fruit seedlings grafted onto seedlings obtained by cuttings or seeds have vigor to be propagated commercially.
Keywords: grafting; irrigation; Passiflora edulis; Passiflora gibertii; Passion fruit